2010
DOI: 10.1097/sla.0b013e3181d773ae
|View full text |Cite
|
Sign up to set email alerts
|

The Intersegmental Plane of the Liver Is Not Always Flat—Tricks for Anatomical Liver Resection

Abstract: The intersegmental plane of the liver has an uneven and curved surface, especially in the right and left portal scissurae. The identification and exposure of the landmark vein on the cut surface is an important technique for avoiding disorientation during anatomic liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 12 publications
3
69
1
1
Order By: Relevance
“…Transection of the liver parenchyma along with the major hepatic vein is considered to be one of the goldstandard methods for anatomic liver resection (6,7). However, present study revealed that the 41.7% was failed to remove entire perfusion area in S6 when the patients was performed based on the hepatic-vein-based anatomy.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Transection of the liver parenchyma along with the major hepatic vein is considered to be one of the goldstandard methods for anatomic liver resection (6,7). However, present study revealed that the 41.7% was failed to remove entire perfusion area in S6 when the patients was performed based on the hepatic-vein-based anatomy.…”
Section: Discussioncontrasting
confidence: 47%
“…However, few reports have so far focused on this essential issue in anatomic liver resection (7,8). We investigate which anatomic factors influenced to such differences and how much parenchymal volume was different between the perfusion areas and drainage area of the liver parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical resection of segment 8 (S8) consists of 28% of all the other segmentectomies, which shows that S8 is the most popular segment that is resected. S8 accounts for 24.2% of the entire liver volume, which is the largest segment [15] . During anatomical resection of S8, the ventral and dorsal glissonean branches of segment 8 are divided, and the MHV and RHV are exposed on the transactional plane as the landmark veins.…”
Section: Important Points For Anatomical Resection Of Segment 8 (Presmentioning
confidence: 99%
“…This watershed zone is always clearly observable in segment VIII, as described in our previous work. 5 However, the drainage pattern of the caudal part of the right paramedian sector (i.e., segment V region) varies among individuals, with V5 occasionally extending to the right lateral sector and draining a proportion of segment VI (n = 8, 8%). Approximately half of the right paramedian sector is drained by MHV (mean proportion, 56.1%), including the drainage region of V8i (mean proportion, 15.6%), with the remaining part drained by RHV (mean proportion, 43.9%).…”
Section: Resultsmentioning
confidence: 99%
“…This precise visualization of the hepatic vascular territories has provided new insights into the surgical anatomy of the liver. 5 The 3D liver analysis is widely used as a component of preoperative work-up for liver resection and transplantation. However, despite recent technical innovations in imaging studies, unexpected intraoperative decision-making is frequently required during complex hepatobiliary surgery and knowledge of the surgical anatomy of the liver remains crucial in such situations.…”
Section: Introductionmentioning
confidence: 99%